Decompressive Hemicraniectomy for Large Hemispheric Strokes. Issue 4 (15th March 2021) - Lin, Jessica; Frontera, Jennifer A.
Abstract : Large hemispheric infarcts occur in up to 10% of all ischemic strokes and can cause devastating disability. Significant research and clinical efforts have been made in hopes of mitigating the morbidity and mortality of this disease. Areas of interest include identifying predictors of malignant edema, optimizing medical and surgical techniques, selecting the patient population that would benefit most from decompressive hemicraniectomy, and studying the impact on quality of life of those who survive. Decompressive surgery can be a life-saving measure, and here we discuss the most up-to-date literature and provide a review on the surgical management of large hemispheric ischemic strokes.